2002
DOI: 10.1159/000066757
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Celiac Adults on Gluten-Free Diet: Prevalence and Correlates of Intestinal Damage

Abstract: Background and Aims: Celiac disease is the most common severe food intolerance in the Western world and is due to gluten ingestion in genetically susceptible children and adults. Intestinal biopsy is the golden standard for evaluation of mucosal damage associated with celiac disease. Gluten-free diet is the key treatment for celiac disease. Data on the long-term control of celiac disease are few and limited to small series of patients. The study reports data on the control of celiac disease and on its correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
216
4
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 219 publications
(236 citation statements)
references
References 18 publications
(24 reference statements)
10
216
4
6
Order By: Relevance
“…Fewer than 50% of adults with CD studied in France and Belgium strictly adhered to a GFD for more than one year after being diagnosed [27]. Similarly, Ciacci et al, in a long-term follow-up study of adults with CD, found that 24% were nonadherent and had severe intestinal damage, while 33% were mildly nonadherent and had milder intestinal damage [17]. Our study population was similar in that fewer than 50% of participants had excellent GFD adherence according to the nutritionist assessment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fewer than 50% of adults with CD studied in France and Belgium strictly adhered to a GFD for more than one year after being diagnosed [27]. Similarly, Ciacci et al, in a long-term follow-up study of adults with CD, found that 24% were nonadherent and had severe intestinal damage, while 33% were mildly nonadherent and had milder intestinal damage [17]. Our study population was similar in that fewer than 50% of participants had excellent GFD adherence according to the nutritionist assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of strict adherence to a GFD in adults have been found to vary between 17% and 45% [16,17,25,26]. Fewer than 50% of adults with CD studied in France and Belgium strictly adhered to a GFD for more than one year after being diagnosed [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations